A Systematic Literature Review: Challenges and Opportunities for Micro, Small, and Medium Enterprises (MSMEs) in the Digital Era - Jessica Aulia Putri; Yulhendri Yulhendri (Universitas KH. Abdul Chalim Mojokerto, 2026)
This systematic literature review explores the challenges and opportunities faced by micro, small, and medium enterprises (MSMEs) in the digital era. The study aims to identify and analyze the challenges and opportunities faced by micro, small, and medium enterprises (MSMEs) in the digital era. The research method used was a comprehensive search of relevant literature using predetermined search criteria, resulting in 320 articles meeting the criteria. These articles were further screened based on their relevance to the research questions, and ultimately, 58 articles were selected for analysis. The results of the study indicate that the digital era offers significant opportunities for MSMEs, particularly in terms of increased access to markets, resources, and information. However, MSMEs also face various challenges, including a lack of digital literacy, limited resources, and intense competition. This study highlights the need for MSMEs to embrace digital technology and develop strategies to address these challenges. Overall, this systematic literature review provides valuable insights into the challenges and opportunities for MSMEs in the digital era and emphasizes the importance of adapting to the changing business landscape. The findings of this study have practical implications for policymakers, MSMEs, and other stakeholders interested in MSME development in the digital era.